Natural ocean alkalinization through erosion of glacial till and weathering at the seafloor: porewater data from AL543 - Florian Scholz; Klaus Wallmann (PANGAEA, 2025)
Climate change-driven deglaciation and erosion in high-latitude regions enhance the flux of terrigenous material to the coastal ocean. Newly exposed land surfaces left behind by retreating glaciers are covered by glacial till, which is rich in fine-grained minerals. Many of these minerals are undersaturated in seawater and thus prone to dissolution (i.e., seafloor weathering). Consequently, intensified erosion and mineral weathering may act as an additional CO? sink while supplying alkalinity to coastal waters. To evaluate this hypothesis, we carried out a sediment geochemical study in the southwestern Baltic Sea, where coastal erosion of glacial till is the dominant source of terrigenous material to offshore depocenters. We analyzed glacial till from coastal cliffs, sediments, and pore waters for major element composition using inductively coupled plasma optical emission spectroscopy and an elemental analyzer. Water samples were further analyzed for dissolved redox species and dissolved silica by photometry and ion chromatography. These data were then used to quantify mineral dissolution and precipitation processes and to assess their net effect on inorganic carbon cycling.